MPC-2 Clinical course and prognosis of lower-grade glioma, IDH wildtype and pTERT mutant. (6th December 2021) - Takahashi, Yoshinobu; Takeuchi, Hayato; Tanigawa, Seisuke; Okamoto, Takanari; Hashimoto, Naoya
Abstract: Background and Purpose: In the cIMPACT-Now update 3, it was proposed that grade 2 astrocytic gliomas without IDH-mutations and grade 3 astrocytic gliomas with TERT promoter mutations should be designated as diffuse IDH wildtype astrocytic glioma with molecular features of WHO grade IV glioblastoma. Therefore, we investigated whether this group of tumors actually corresponds to grade IV prognostically in cases that we encountered ourselves. Cases and Methods: Among the 65 patients having primary astrocytic glioma who were operated in our hospital from January 2016 to March 2021, the prognostic values of seven patients with lower-grade glioma, IDH wildtype, and pTERT mutant were investigated. Results: Among the seven patients, the median age was 59 years (50–66 years). Four of them had anaplastic astrocytoma, two had diffuse astrocytoma, and no tumor lesion could be identified upon histological examination for one patient. The male-to-female ratio was 1:6. MGMT methylation was observed in two patients (29%). The median survival was 20 months, with a significantly worse prognosis when compared with lower-grade glioma without the TERT promoter mutation (13 patients: median survival 40 months), but a better prognosis when compared with glioblastoma (45 patients: median survival 13 months) (Log-rank p = 0.0051). Conclusion: Although EGFR amplification, combined whole chromosome 7 gain, and whole chromosome 10 loss were not examined, the prognostic value of lower-grade glioma, IDH wildtype, and pTERT mutant was not as poor as that of glioblastoma. Further investigation is required to confirm whether these groups of tumors should be treated in the same way as grade IV glioblastoma.